Lokal menigheter i lokale samfunn (Nordic Journal of Practical Theology, 2021)
Starting with the particularly strong attention which used to be given to the local community in our elementary school, and with Norway’s reputation as a country with a selfconfident periphery, the first part of this article aims at reaching a viable understanding of what a local community is, of the applicability of this general theory to the local church, and of the interaction between church and community. The theoretical framework is an adaptation of Norbert Elias’ figuration sociology as developed by historian Knut Kjeldstadli, and the analysis is guided by Robert Putnam’s theory on the formation and deterioration of social capital. The second and final part of the article turns to the reports provided by Prosjekt kirkelig organisering, and offers a critical reading of their overly institution-oriented understanding of the local church as well as of the local community.